Fretting fatigue lifetime estimation using a cyclic cohesive zone model. (January 2020) - Pereira, K.; Abdel Wahab, M.
Abstract: Over the past decades, many numerical procedures aiming to predict the life of components subjected to fretting fatigue have been developed. Most procedures combine estimates of crack initiation and propagation lives in order to obtain total lifetime. Nevertheless, crack initiation life estimates are generally not easy to define. An alternative is to consider the failure in a cycle-by-cycle analysis using cyclic cohesive zone model (CCZM), accounting for loading and unloading damage accumulation at crack front. However, a cycle-by-cycle analysis is extremely computational demanding. To overcome this issue, we propose an extrapolation procedure in junction with CCZM for the crack propagation modelling, which is substantially faster than a complete cycle-by-cycle analysis. This approach is compared, in terms of accuracy of life estimates, to traditional linear elastic fracture mechanics and experimental data. Highlights: Cyclic cohesive zone model (CCZM). Crack propagation lifetime prediction. Taking into account loading and unloading damage accumulation at crack front. Extrapolation procedure in junction with CCZM for the crack propagation modelling.